Thermal Mining of volatiles in lunar regolith simulant. (1st November 2022) - Purrington, C.; Sowers, G.; Dreyer, C.
Abstract: Volatiles such as water trapped in lunar Permanently Shadowed Regions (PSR) are key to the sustainability of space exploration and will underpin most economic activities in space. Thermal Mining is a technique to efficiently extract certain volatiles without excavation. This paper discusses experimental results applying Thermal Mining to extracting water ice from lunar regolith simulant using thermal energy from a lamp. Lunar Highlands Simulant was mixed with different water ice configurations and chilled to cryogenic temperatures (<100K). The temperature was maintained in a vacuum chamber through the use of Liquid Nitrogen (LN) in a cryogenic container. A halogen lamp represented a 'sun source' and the output power was adjusted to be equivalent to the optical output of 0.1371W/cm^2. The experimental results show that extraction of volatiles with Thermal Mining is effective at exhausting ice in the top 2 ​cm of lunar regolith and may be effective at greater depths given more time. The results also show that some ice that has been vaporized escapes through the surface and is effectively harvested, while a portion of the water vapor travels throughout the regolith and is redeposited as different ice structure (vapor deposition). The use of submerged heating rods was also explored to increase ice yield and deliver heat further into the icy regolith bed. This paper concludes that Thermal Mining maybe a desirable alternative to traditional mining operations which require high mass excavation vehicles and many moving parts.